Implementasi Metode Naive Bayes Dalam Pengelompokkan Data Penyakit Berdasarkan Indeks Masa Tubuh Pada Puskesmas Babatan - Doni Johan Gultom; Khairil Khairil; Eko Suryana (Jurnal Media Infotama, 2025)
The purpose of this study is to apply the naïve bayes algorithm for classifying Body Mass Index at the General Polyclinic of the Babatan Health Center UPTD. The diagnosis of Body Mass Index is one of the diagnoses with severe conditions that are often complained about at the Babatan Health Center Polyclinic. However, the problem in its service is still very limited because doctors are only on duty for 2 days in one week. Therefore, a method is needed that is able to classify the level of risk of Body Mass Index that occurs at the Babatan Health Center UPTD so that it can be handled immediately with appropriate actions using the Naïve Bayes method. From the results of the tests carried out, the Naïve Bayes method can be used as a solution in using this system. In its application, the Naïve Bayes method can classify the type of Body Mass Index at the Babatan UPTD